2013
DOI: 10.1158/0008-5472.can-12-1343
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Response Protein RBM3 Attenuates the Stem-like Properties of Prostate Cancer Cells by Interfering with CD44 Variant Splicing

Abstract: Stress-response pathways play an important role in cancer. The cold-inducible RNA-binding protein RBM3 is upregulated in several types of cancer, including prostate cancer, but its pathogenic contributions are undetermined. RBM3 is expressed at low basal levels in human fetal prostate or in CD133 þ prostate epithelial cells (PrEC), compared with the adult prostate or CD133-PrEC, and RBM3 is downregulated in cells cultured in soft agar or exposed to stress. Notably, RBM3 overexpression in prostate cancer cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 46 publications
5
51
0
Order By: Relevance
“…Herein, a significantly decreased 5-year OS was demonstrated for patients with tumours displaying low expression of RBM3, which is well in line with previous findings in UBC [26], as well as breast cancer [17], epithelial ovarian cancer [18, 30], prostate cancer [19, 21], testicular cancer [25], oesophageal and gastric cancer [23] and melanoma [24]. …”
Section: Discussionsupporting
confidence: 90%
“…Herein, a significantly decreased 5-year OS was demonstrated for patients with tumours displaying low expression of RBM3, which is well in line with previous findings in UBC [26], as well as breast cancer [17], epithelial ovarian cancer [18, 30], prostate cancer [19, 21], testicular cancer [25], oesophageal and gastric cancer [23] and melanoma [24]. …”
Section: Discussionsupporting
confidence: 90%
“…This modification leads to an inability to degrade β-catenin and results in nuclear accumulation of β-catenin, thus activating the β-catenin signaling pathway [47]. However, another study suggested that high RBM3 attenuated the stemness and tumorigenesis by inhibiting CD44 variant splicing in prostate cancer cells [48]. The possible mechanism proposed by the authors is that RBM3 in cancers involves in enhancing the balance between CD44v and CD44s expression to attenuate the stem cell like features to adapt to the change in the microenvironment for survival and repopulation of tumor cells.…”
Section: Rbm3 In Cancermentioning
confidence: 99%
“…Moreover, in epithelial ovarian cancer a link between reduced RBM3 levels and sensitivity to platinum based chemotherapy has been demonstrated in vitro and in vivo [6]. While the mechanistic basis for the association between high RBM3 expression and good prognosis needs to be further elucidated, some directions may be provided by the observed association between RBM3 expression and DNA integrity and repair [12], and the ability of RBM3 to attenuate stem-cell like properties of prostate cancer cells [13]. …”
Section: Introductionmentioning
confidence: 99%